Larvicidal Effect of Vinca Fruit Extract (Vinca rosea) Against Aedes aegypti Larvae and Secondary Metabolites Profile by Thin Layer Chromatography - Rahmawati Ekaputri; Sudarsono Sudarsono; Budi Mulyaningsih (Biology, Medicine, & Natural Product Chemistry, 2014)
Background: Vinca rosea is known contain alkaloids, it was usually used to treat various diseases. Alkaloids from Vinca leaves are also already known have larvicidal activity. Based on this toxicological activity, the fruit of Vinca rosea was selected to investigation its larvicidal activity against the 3rd instar larvae of the mosquito vector of dengue haemorrhagic fever (DHF) Aedes aegypti.  Five concentrations of Vinca fruit extract were tested against the 3rd instar Aedes aegypti larvae. The different larval mortality percentages were recorded after 24 hours. Lethal concentration (LC50 anf LC90) of Vinca fruit extract were calculated using Probit analysis. Phytochemical compounds  of ethanolic extract also investigated using Thin layer Chromatography (TLC). LC50 and LC90 values of fruit extract were 2.987 mg/ml and 32.861 mg/ml. Alkaloids were detected in extract.